BOARDING SCHOOL EDUCATION: CONTROVERSY IN BRITAIN AND SITUATION IN PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Britain has a time-honoured tradition of boarding school education. Some reputed schools have included Eton and Harrow whose students went on to become Prime Ministers, famous generals, and other men of public affairs. The tradition expanded to territories of the British Empire including British India of late. The system of boarding school education has come under criticism. The system is alleged to have promoted/ perpetuated elitism and inequity in society. More damning criticism relates to the insufferable impact on the mental health of several boarders. It has been argued by professional psychotherapists that induction in boarding school at an early stage is accompanied by a series of emotional ruptures often leading to such psychological problems as have been summed up in the phrase ‘Boarding School Syndrome’. Newer research at some centres of psychology in Britain, based on surveys and in-depth interviews of ex-boarders has tended to challenge the boarding school syndrome concept catapulted by psychotherapist literature, on two main counts: (1) the new research emphasizes more than the previous literature that younger the child at the time of induction, the more traumatic the boarding school experience, and (2) the border that enjoyed the boarding school, took the boarding house to better than their home environment which, one way or the other, came to lose its charm for them. Pakistan inherited the boarding school tradition since colonial times. The literature relating to boarding schools in Pakistan tends to be more in consonance with the two findings of the post-syndrome literature in Britain. The present study reviews both the controversy in Britain and the literature from Pakistan. It contributes to the subject of boarding school education by utilizing two sources. These comprise, firstly, of extensive personal experiences of two of the authors as teachers, housemasters and principals at several boarding schools/colleges in Pakistan including cadet colleges. The third author possessed knowledge of Eton and Harrow during his school education in Pakistan, lived in Britain for a decade, served there for five years as a lecturer in English and Communication Skills and visited famous Boarding schools. The study thus seeks to provide comparative context to the discussion related to the boarding school education controversy.